The Effectiveness of Organic Fertilizer Granules for Increasing Sweet Corn Production on Acid Dryland In Bogor District - Regina Intansari, Rr Salsabila; Subiksa, IGM (Journal of Soilscape and Agriculture, 2022)
Acid dry land generally has limiting factors of higher acidity and low nutrients availibity, so that has low productivity. However, the appropriate inputs have productivity to be better. Research on effectivness of granular organic fertilizers (GOF) to increase sweet corn production has been carried out on dry land in Bogor Regency. The purpose research was to determine the effect GOF of plant growth and enhancment production of sweet corns in acid dry land. This study used a Completely Randomized Block Design with ten treatments and three replications. The results showed that the application of GOF dose 200 kg/ha could increasing soil pH. This improvement in soil chemical properties was followed by increased growth and production of sweet corn. Besides increase the plant growth, GOF made more efficiency 25% of anorganic fertilizer usage. The combination treatment of granular organomineral fertilizers dose 600 kg/ha and NPK recommendation 75% fertilizers increase plant growth such as plant height (124,52%), number of leaves (49%), and plant stem diameter (84,3%). The combination treatment of granular organomineral fertilizers dose 200 – 400 kg/ha and NPK recommendation 75% fertilizers increase sweet corn production such fresh cobs production (345%) and dry corn stover (345%). RAE value is >100% in each GOF treatment, which is the fertilizer effective to increase the sweet corn crops. The optimum yield of maize is 17,45 ton/ha could be obtained with the application of granular organomineral fertilizers dose 275 kg/ha.